Sine-Squared pulse approximation using generalized bessel polynomials - Thanavit Anuwongpinit; Vanvisa Chutchavong; Kanok Janchitrapongvej; Chawalit Benjangkaprasert (My University, 2019)
This paper presents the approximation of sine-squared pulse based on the generalized Bessel polynomials. For designing a circuit to synthesize a sine-squared pulse test signal. The generalized Bessel polynomials have more parameter than classical Bessel polynomials that have alpha and beta parameters for adjusting the dominator of the transfer function to approximate the sine-squared pulse that closes to the ideal pulse. The simulation results show that the generalized Bessel polynomial can adjust the approximation response close to the ideal response. The orders of the transfer function are decreased that confirm a better performance than the previous works.
Keywords: Bessel polynomials; Sine; Bessel process; Sensor Technology and Measurement Systems